Komunikasi Lingkungan dalam Pencegahan Kebakaran Hutan dan Lahan Lingkungan Hidup dan Kehutanan Provinsi Riau - Edy Zaputra; Emeraldy Chatra; Ernita Arif (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
Indonesia faces significant challenges concerning deforestation, with forest and land fires emerging as a prominent contributor to deteriorating air quality and subsequent health concerns, notably evident in Riau Province where these fires are recurrent. This study endeavors to scrutinize the Environmental and Forestry Service of Riau Province's environmental communication strategies aimed at preventing forest and land fires and to unravel the underlying motives guiding these communication efforts. Employing a qualitative methodology and a phenomenological approach to examine environmental communication as a mechanism for forest and land fire prevention, the study adopts an interpretive phenomenological data analysis approach. Findings from the research elucidate that DLHK Riau Province employs patrolling and awareness campaigns to communicate the legal prohibition of forest burning, supplemented by supervision and engagement with companies situated in fire-prone regions. Moreover, the provision of forest plant seeds seeks to counteract the expansion of oil palm plantations. The study highlights challenges faced by DLHK in conducting effective environmental communication due to budget constraints and geographical barriers to reaching remote communities. It further underscores the motivation behind environmental communication, rooted in operational and technical guidelines, particularly pertinent in Riau Province, where extensive peatlands necessitate specialized management and intervention.